ISLAMIC SOCIAL FINANCE SEBAGAI SOLUSI KRISIS EKONOMI GLOBAL - Yaqin, Abdullah; Muzaki, Mohammad (Mozaic: Islamic Studies Journal, 2025)
The global economic crisis triggered by the pandemic, geopolitical conflicts, and recessions has significantly impacted various economic sectors, particularly in developing countries. Conventional financial systems are often deemed ineffective in addressing crises due to weak regulations and policies that focus more on mitigating impacts rather than resolving root causes. In this context, Islamic Social Finance (ISF) emerges as a more inclusive and sustainable solution through instruments such as zakat, waqf, sadaqah, and qardhul hasan. This study adopts a literature review approach to explore the role of ISF in addressing the global economic crisis and its contribution to economic growth and financial inclusion. The findings indicate that ISF plays a strategic role in enhancing socio-economic welfare by distributing funds to vulnerable groups, supporting MSME growth, and financing social projects through social sukuk and productive waqf. The implementation of ISF in countries such as Indonesia and Malaysia has proven effective in aiding post-crisis economic recovery and reducing social inequality. Therefore, optimizing ISF management through collaboration between governments, philanthropic institutions, and the private sector is essential to ensure that Islamic financial instruments contribute more significantly to building a stable and sustainable economic system.